PENINGKATAN PEMBELAJARAN TEMATIK MENULIS PANTUN BERBANTUAN PENDEKATAN SCIENTIFIC PADA SISWA KELAS V SDN 002 SAMARINDA TAHUN AJAR 2016/2017 - Hety Diana Septika; Mohammad Ilyas (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Balikpapan, 2019)
This research is motivated by the difficulty of applying writing learning in the 2013 curriculum which experiences gaps. The difficulty of applying K13 with the many assessments in K13 has made teachers reluctant to use K13 learning. Learning Indonesian in K2013 has an important role, one of which is writing skills. One of the skills taught in elementary schools is poetry writing. Poetry writting is important to be taught because in addition to being a cultural heritage, it also needs to be preserved and known by children especially Elementary School.